2016
DOI: 10.5301/hipint.5000353
|View full text |Cite
|
Sign up to set email alerts
|

Good Mid- to Long-Term THA Outcomes with a Modified Cementless Rectangular Biconical Stem Design

Abstract: The cementless proximal press-fit femoral stem was associated with good mid- to long-term survival and functional outcomes. The current design can be considered equivalent to the second- and third-generation Zweymüller stems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The results of a clinical evaluation of the Fitmore (Zimmer) stem showed a HHS of 99.0 with a mean follow-up of 2 years and 3 revisions in the same period of time [9]. The evaluation of the PPF (proximal press-fit) (Biomet) stem in a cohort of 142 patients was published in 2016 [10]. Iori and Vigano showed a survivorship of 99.1% after 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a clinical evaluation of the Fitmore (Zimmer) stem showed a HHS of 99.0 with a mean follow-up of 2 years and 3 revisions in the same period of time [9]. The evaluation of the PPF (proximal press-fit) (Biomet) stem in a cohort of 142 patients was published in 2016 [10]. Iori and Vigano showed a survivorship of 99.1% after 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evaluation (using the HHS and VAS for pain) showed that patients experienced substantial improvements in health, although not as good as afforded by their primary operations, in agreement with the data of others who have reported clinical outcomes following placement of the tapered rectangular femoral stem. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evaluation (using the HHS and VAS for pain) showed that patients experienced substantial improvements in health, although not as good as afforded by their primary operations, in agreement with the data of others who have reported clinical outcomes following placement of the tapered rectangular femoral stem. 34,35 Similarly to the Wagner stem, this stem shares with the SLR-Plus stem the principle of obtaining an immediate tight fit and mechanical stability through diaphyseal fixation of a long titanium alloy stem with a rough-blasted surface. In a series of 79 hips using Wagner stem, Gutierrez et al 7 reported subsidence in 16 at an average of 6 years after surgery, of which 1 exhibited subsidence >20 mm, and the stem subsidence is associated with excessive weight-bearing during the first 3 postoperative months.…”
Section: Discussionmentioning
confidence: 99%
“…Rectangular postoperatively by the baseline value. The values were expressed as area BMD in g/cm 2 .…”
Section: Characteristicmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is an effective surgical procedure for treatment of end-stage hip osteoarthritis, osteonecrosis, and rheumatoid arthritis and can effectively improve function and reduce pain 1 . Cementless fixation is a standard fixation method and has been reported to have excellent midterm results 2,3 . Furthermore, cementless short-stem total hip arthroplasty can preserve femoral bone stock, address stress shielding effects, and provide a greater physiological load transfer than traditional THA, and its use has been on the rise in recent years 4,5 .…”
Section: Introductionmentioning
confidence: 99%